2017
DOI: 10.1371/journal.pone.0171205
|View full text |Cite
|
Sign up to set email alerts
|

A single-arm, open-label, phase 2 clinical trial evaluating disease response following treatment with BI-505, a human anti-intercellular adhesion molecule-1 monoclonal antibody, in patients with smoldering multiple myeloma

Abstract: BackgroundSmoldering multiple myeloma (SMM) is an indolent disease stage, considered to represent the transition phase from the premalignant MGUS (Monoclonal Gammopathy of Undetermined Significance) state towards symptomatic multiple myeloma (MM). Even though this diagnosis provides an opportunity for early intervention, few treatment studies have been done and the current standard of care is observation until progression. BI-505, a monoclonal antibody directed against intercellular adhesion molecule 1 (ICAM-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The first one entailed a Phase I dose-escalation study in patients suffering from advance relapsed/refractory multiple myeloma ( 49 ). The second assay consisted in an open arm-phase 2 clinical trial enrolling four patients diagnosed with smoldering multiple myeloma and showed no relevant clinical activity although treatment was well tolerated ( 50 ). Interestingly, a Phase I/II study of BI-505 in conjunction with autologous stem cell transplant in multiple myeloma (NCT02756728) was terminated due to and adverse cardiopulmonary event in the clinical study (as reported in the informative press note released by BioInvent in November 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The first one entailed a Phase I dose-escalation study in patients suffering from advance relapsed/refractory multiple myeloma ( 49 ). The second assay consisted in an open arm-phase 2 clinical trial enrolling four patients diagnosed with smoldering multiple myeloma and showed no relevant clinical activity although treatment was well tolerated ( 50 ). Interestingly, a Phase I/II study of BI-505 in conjunction with autologous stem cell transplant in multiple myeloma (NCT02756728) was terminated due to and adverse cardiopulmonary event in the clinical study (as reported in the informative press note released by BioInvent in November 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As a novel synergistic tumor immune escape was exerted by ICAM-1 and TGFβ2 signal, it opens a new potential in translational application. Interestingly, some clinical trials have been initiated to target ICAM-1 and TGFβ2 individually as the possibilities for future cancer immunotherapies [ 48 , 49 ]. This can further lead into combinations of immunotherapy as new strategies against cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Enlimomab (BIRR1/R6.5), another anti-human ICAM-1 antibody, was also tested in clinical trials to treat rheumatoid arthritis, prevent acute rejection of renal transplants and in acute stroke patients, and showed some clinical improvements for arthritis as well as stroke patients and importantly good tolerability [ 59 , 60 ]. The first human anti-ICAM-1 IgG1 mAb BI-505 was recently evaluated in clinical trials for patients with relapsed/refractory MM and smoldering myeloma [ 61 , 62 ]. Even though future clinical development was stopped, BI-505 was mostly well tolerated.…”
Section: Discussionmentioning
confidence: 99%